PROSPECTS FOR COMPLETION OF INCOMPLETE BUILDING OBJECTS - A. Kozlovskii; N. Moiseenko (Вестник университета)
Actual problems of not complete building in modern economic conditions have been considered in the article. Questions of land tenure and allocation of sites under not completed objects, strategy of expenses in this segment, state sale and others are consistently have been analysed. Principles and approaches to the analysis of volumes of not complete building with their preliminary estimation for the further alternative use have been defined. Comparative variants of completion of incomplete building objects, the analysis and an estimation of external conditions have been presented. The attention has been paid to possibilities of the state-private partnership and projects of completion of incomplete building objects. Questions of distribution of shares between participants of completion and the further operation of such objects have been considered. Offers under the decision of tasks in view have been provided.